1993
DOI: 10.1111/j.1365-2249.1993.tb06497.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent cellular cytotoxicity and neutralizing activity in sera of HIV-1-infected mothers and their children

Abstract: SUMMARYThe prognostic and protective role of antibodies mediating cellular cytotoxicity (ADCC) and neutralization was evaluated in sera of HIV-1-infected mothers and their consecutively followed children. The presence and titres of ADCC mediating and/or neutralizing antibodies in maternal sera did not predict HIV-1 infection in their respective children. No significant diflFerence in the sera from the children was seen when comparing the presence of neutralizing antibodies between the uninfected and infected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…For this purpose, the relationships between the risk of vertical transinission and the presence of maternal antibodies inducing ADCC and viral neutralization on MDM and PBMC were investigated. Questions remain about the relevance of antibodies mediating viral neutralizaton and ADCC in the HIV-1 vertical transmission process, Wilh this in mind, ADCC was examined in 47 sera of HlV-1-infected mothers using PBMC as effector cells, but not PBL as reported elsewhere [18]. Here, we show that measurable ADCC fitres against HIV-1-infected cells were present in over 80% of HIV-1-infected mothers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For this purpose, the relationships between the risk of vertical transinission and the presence of maternal antibodies inducing ADCC and viral neutralization on MDM and PBMC were investigated. Questions remain about the relevance of antibodies mediating viral neutralizaton and ADCC in the HIV-1 vertical transmission process, Wilh this in mind, ADCC was examined in 47 sera of HlV-1-infected mothers using PBMC as effector cells, but not PBL as reported elsewhere [18]. Here, we show that measurable ADCC fitres against HIV-1-infected cells were present in over 80% of HIV-1-infected mothers.…”
Section: Discussionsupporting
confidence: 59%
“…They may represent a way of entry and/or a reservoir for viruses in the fetus of pregnant HlV-l-infected women [17]. Otherwise, the role of antibodies mediating antibody-dependent cell-mediated cylotoxicity (ADCC) in infected mothers and their relationships to the HIV infection of the infant have been documented in only one study using purified peripheral blood lymphocytes (PBL) as eflector cells [18]. Therefore, our study was conducted to assess the reUuionship between ADCC, neutralizing antibodies in HlV-l-inlected mothers, and the occurrence of HIV infection in the infant.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of antibodies capable of mediating neutralization or antibody-dependent cell-mediated cytotoxicity (ADCC) in infants has been associated with better clinical outcome (46,47); however, infants infected in utero rarely develop ADCC antibodies before 12 months of age (48). Interestingly, while a delay in the development of ADCC-mediating responses is also observed in infants infected during the first 6 weeks of life, ADCC antibodies can be detected as early as 2 months postinfection when infants are infected later in life (46).…”
Section: Immune Responses To Hiv Infection In Infants and Adultsmentioning
confidence: 99%
“…Baum et al, (1996) presented strong evidence that higher titers of antibodies mediating ADCC correlated with a successful host defense against HIV-1, and Forthal et al, (2001a) reported an inverse association between ADCC activity and plasma viremia. Higher ADCC activity has also been correlated with slower disease progression in children (Ljunggren et al, 1990;Broliden et al, 1993). More recently, ADCC activity has been demonstrated in cervical lavage fluids of HIV-infected women (Battle-Miller et al, 2002), and associated with lower genital HIV RNA loads (Nag et al, 2004).…”
Section: Hiv-specific Adcc Responses In Natural Infectionmentioning
confidence: 98%